Korean Brain Rehabilitation Registry for Rehabilitation of Persons with Brain Disorders: Annual Report in 2009 - Yang, Seung Nam (The Korean Academy of Medical Sciences, 2012)
This first annual report provides a description of patients discharged from rehabilitation facilities in Korea based on secondary data analysis of Korean Brain Rehabilitation Registry V1.0 subscribed in 2009. The analysis included 1,697 records of patients with brain disorders including stroke, traumatic brain injury, brain tumor and other disorders from 24 rehabilitation facilities across Korea. The data comprised 1,380 cases of stroke, 104 cases of brain injury, 55 cases of brain tumor, and 58 cases of other brain diseases. The functional status of each patient was measured using the Korean version of the Modified Barthel Index (KMBI). The average change in the KMBI score was 15.9 for all patients in the inpatient rehabilitation facility. The average length of stay for inpatient rehabilitation was 36.9 days. The transfer rates to other hospitals were high, being 62.4% when all patients were considered. Patients with brain disorders of Korea in 2009 and measurable functional improvement was observed in patients. However, relatively high percentages of patients were not discharged to the community after inpatient rehabilitation. Based on the results of this study, consecutive reports of the status of rehabilitation need to be conducted in order to provide useful information to many practitioners.